Analysis of Factors that Form the Surplus of Last Year's Budget Calculation (SiLPA) In the Mataram City Regional Budget for the 2012 - 2022 Period - Janna, Ilza Lail Fatul; Yasin, Muaidy; Sujadi, Sujadi (The Es Economics and Entrepreneurship, 2024)
This study is entitled "Analysis of Factors Forming the Surplus of Last Year's Budget Calculation (SiLPA) in the Mataram City Regional Budget for the 2012-2022 Period". The purpose of this study is to analyze whether the excess of PAD, excess of balancing funds, excess of financing, and remaining savings in spending affect SiLPA partially or simultaneously. This type of research is a quantitative descriptive study, namely describing the remaining budget calculations carried out to determine the value of the independent variables that significantly affect the dependent variable. The data used are secondary data analyzed by statistical analysis. The analysis tool used in this study uses multiple linear regression statistical tests. The results of the study concluded that the excess of PAD, excess of balancing funds, excess of financing, and remaining savings in spending significantly affect SiLPA in the Mataram City Regional Budget for the 2012-2022 period in partial tests (alone) and simultaneous tests (together).